Quasi‐Two‐Dimensional Ferromagnetic SrRuO3 Grown by Pulsed Laser Deposition with Layer‐by‐Layer Growth Fashion. Issue 30 (12th September 2022) - Deng, Zhixiong; Liu, Junhua; Hong, Yuhao; Wei, Long; Hu, Shilin; Xiao, Wen; Li, Lin; Wang, Lingfei; Chen, Kai; Liao, Zhaoliang
Abstract: One of the keys to the construction of metal oxide heterostructures is the short characteristic length scale, which requires controlled growth and interface engineering on an atomic level. At present, the growth mode of SrRuO3 (SRO) thin films grown on TiO2 ‐terminated (001) SrTiO3 (STO) substrates usually transitions from 2D layer‐by‐layer to step‐flow at the first few growth periods, which is not conducive to the construction of superlattices or multilayer films. In this paper, persistent layer‐by‐layer growth of SRO thin films is demonstrated by regulating the growth conditions. As a result, the thickness can be precisely controlled down to a single unit cell (u.c.) and achieve precise regulation of superlattices. Interestingly, the physical properties are well comparable to that of traditional step‐flow mode and the critical thickness ( tc ) for the dead layer is only 3 u.c. Through constructing SRO/STO superlattices, the SRO layers become more conductive and a quasi‐2D ferromagnetic monolayer film is achieved. The results pave a path toward SRO heterostructure synthesis and properties control at an atomic scale. Abstract : This paper demonstrates a persistent layer‐by‐layer growth mode of SrRuO3 (SRO) films fabricated by pulsed laser deposition. Relying on this mode, the thickness of SRO superlattices can be precisely controlled down to a single unit cell and a quasi‐2D ferromagnetic monolayer film is achieved. The results pave a path toward SRO heterostructure synthesis and properties control at an atomic scale.